(untitled) (Jurnal Ecosolum, 2020)
The development of industries and settlements along the Wanggu River and several other rivers that flow into Kendari Bay have affected the quality of river water and have an impact on the deterioration in the quality of water resources and the environment. The decline in water quality is characterized by changes in physical water, namely changes in water color, odor, and taste. A river is said to be polluted if its water quality is not in accordance with its designation. The purpose of this study was to determine the abundance of macrozoobenthos and the quality of river water which empties into Kendari Bay. This study uses a survey method, the information collected at each trailer station represents the entire population. Sampling uses a purposive sampling method with five replications per station. Sampling of macrozoobenthos, measurement parameters namely temperature, pH, DO, COD, BOD, organic matter, Substrate. Based on macrozoobenthos observations found during the study consisted of 16 types, which were classified into 5 classes and 3 phyla with composition Bivalvia (43.75%)class Gastropod (25%), and Polychaeta (18.75%), Insect Class (6, 25%) and Oligochaeta Class (6.25%) with macrozoobenthos density values ranging from 25 - 125 Ind / m². Diversity index values at the six stations are categorized as low diversity with an average value of H ’= 1.27. The river that flows into Kendari Bay is polluted, this is confirmed by the results of environmental chemical tests. Parameters that exceed quality standards for Class II waters are COD and BOD.